Latitudinal gradients and diversity of the leaf-cutting ants (Atta and Acromyrmex) (Hymenoptera: Formicidae) - Fowler, Harold G. (1983)
Current biogeographic patterns of the 12 genera of the gardening ant tribe Attini are examined. Six of the genera are more concentrated in the southern subtropics of South America, and the true leaf-cutting ants, Atta and Acromyrmex, markedly so. No pattern of taxonomic diversity following phylogeny emerges, and the hypothesis that leaf-cutting ants evolved in the tropical rain-forest cannot be assumed to be confirmed. The taxonomic diversity of attine ants on Caribbean islands was examined in terms of biogeographic theory. Island surface area and distance from the mainland were important in predicting species numbers present, yet these two factors only explained less than 50% of the observed taxonomic diversity.